OsTPS8 controls yield‐related traits and confers salt stress tolerance in rice by enhancing suberin deposition. Issue 3 (5th October 2018) - Vishal, Bhushan; Krishnamurthy, Pannaga; Ramamoorthy, Rengasamy; Kumar, Prakash P.
Summary: Class I TREHALOSE‐PHOSPHATE‐SYNTHASE ( TPS ) genes affect salinity tolerance and plant development. However, the function of class II TPS genes and their underlying mechanisms of action are unknown. We report the identification and functional analysis of a rice class II TPS gene ( OsTPS8 ). The ostps8 mutant was characterised by GC‐MS analysis, an abscisic acid (ABA) sensitivity test and by generating transgenic lines. To identify the underlying mechanism, gene expression analyses, genetic complementation and examination of suberin deposition in the roots were conducted. The ostps8 mutant showed salt sensitivity, ABA sensitivity and altered agronomic traits compared to the wild‐type (WT), which could be rescued upon complementation. The dsRNAi line phenocopied the mutant, while the overexpression lines exhibited enhanced salt tolerance. The ostps8 mutant showed significantly reduced soluble sugars, Casparian bands and suberin deposition in the roots compared to the WT and overexpression lines. The mutant also showed downregulation of SAPKs (rice SnRK2s ) and ABA‐responsive genes. Furthermore, ostps8pUBI::SAPK9 rescued the salt‐sensitive phenotype of ostps8 . Our results suggest that OsTPS8 may regulate suberin deposition in rice through ABA signalling. Additionally, SAPK9‐mediated regulation of altered ABA‐responsive genes helps to confer salinity tolerance. Overexpression of OsTPS8 was adequate to confer enhanced salinity tolerance without any yield penalty, suggesting its usefulness in rice genetic improvement.